(untitled) - Edmir Daniel Carvalho; Igor Paiva Ramos; Alison Carlos Wunderlich; Gislayne de Melo Toledo; Heleno Brandão; Reinaldo Jose da Silva (Revista Brasileira de Parasitologia Veterinária, 2013)
The occurrence of the cymothoidae Braga cigarra is reported parasitizing the oral cavity of freshwater fish Galeocharax knerii from Veados, Paranapanema and Taquari Rivers, affluent of the Jurumirim Reservoir, State of Sao Paulo, Brazil is reported. The isopod species were identified based on the multilaminar pleopods, narrow pleon and short pleotelson in females. The overall prevalences of isopods were 31.7%, 7.7% and 5.7%, respectively, in the Paranapanema, Veados and Taquari Rivers. This note contributes to the knowledge of the geographical distribution and fauna of parasite crustaceans known to date in these important ecosystems. Foi registrada a ocorrência do cymothoidae Braga cigarra parasitando a cavidade bucal do peixe de água doce Galeocharax knerii capturado nos rios Veados, Paranapanema e Taquari, afluentes da represa de Jurumirim, Estado de São Paulo, Brasil. As espécies de isópodas foram identificadas com base nos pleópodos multilaminares, abdômen estreito e pleotelson curto nas fêmeas. As prevalências totais de isópodos foram 31,7%, 7,7% e 5,7%, respectivamente, nos rios Paranapanema, Veados e Taquari. Essa nota contribui com o conhecimento da distribuição geográfica e da fauna de crustáceos parasitas conhecidas até a presente data nesses importantes ecossistemas aquáticos.